Distribution of squeezed states through an atmospheric channel - Peuntinger, Christian; Heim, Bettina; Mueller, Christian R.; Gabriel, Christian; Marquardt, Christoph; Leuchs, Gerd (Physical Review Letters, 2014)
Continuous variable quantum states of light are used in quantum information protocols and quantum metrology and known to degrade with loss and added noise. We were able to show the distribution of bright polarization squeezed quantum states of light through an urban free-space channel of 1.6 km length. To measure the squeezed states in this extreme environment, we utilize polarization encoding and a postselection protocol that is taking into account classical side information stemming from the distribution of transmission values. The successful distribution of continuous variable squeezed states is accentuated by a quantum state tomography, allowing for determining the purity of the state. © 2014 American Physical Society.
CRIS-Team Scopus Importer:2022-06-05